Kernel position effects of grain morphological characteristics by X-ray micro-computed tomography (μCT) - Yin, Xuebo; Hou, Junfeng; Ming, Bo; Zhang, Ying; Guo, Xinyu; Gao, Shang; Wang, Keru; Hou, Peng; Li, Shaokun; Xie, Ruizhi (International Journal of Agricultural and Biological Engineering, 2021)
Grain size and shape are important factors for yield and quality. The difference in grain phenotypic characteristics in the same maize hybrid is related to its position in the ear. This study aimed to clarify the distribution characteristics of grain morphological characteristics in the ear and to provide guidance for research of grain phenotype and kernel position effects. Three maize hybrids were used in the experiment, namely, Denghai 618 (DH618), KX3564, and Xianyu 335 (XY335), and the kernel number per row were 40, 40, and 36, respectively. The X-ray μCT was applied to obtain five kernel morphological indicators, including grain length, width, thickness, volume, surface area. Grain sphericity, length-width ratio, specific surface area, and volume coefficient were further calculated. The results showed that there were three types of maize ear morphological indicators trends: grain length, width, volume, and surface area were parabolic; thickness and sphericity were inverted parabolic; length-to-width ratio and specific surface area were irregular. The volume coefficient of grain at different parts of the ear, namely the relation coefficient between grain volume and grain length, width, and thickness, was determined. The average value of the middle grains morphological indicators of the ear was taken to select kernels representing stable characteristics of the variety. Within the range of 5% deviation from the morphological mean value of the middle grains of the ear, the grains in the middle part accounted for 26.39% of the total ear, about 10 grains extending from the 14th grain at the base of the ear to the top. Within the range of 10% deviation, the middle accounted for 47.22%, about 18 grains extending from the 12th grain at the base of the ear to the top. This study found that grain morphological indicators were greatly different at different positions of the maize ear, and showed different change rules as extend from the base to the top of the ear. Therefore, there were different grain volume coefficients at different positions of maize ear. And the representative sampling range on maize ear was determined based on the comprehensive analysis of different morphological indexes variation of grain. Keywords: grain morphology, X-ray μCT, kernel position effects, maize (Zea Mays L.) DOI: 10.25165/j.ijabe.20211402.6039 Citation: Yin X B, Hou J F, Ming B, Zhang Y, Guo X Y, Gao S, et al. Kernel position effects of grain morphological characteristics by X-ray micro-computed tomography (μCT). Int J Agric & Biol Eng, 2021; 14(2): 159–166.